Cerebrospinal Fluid S100B and Alzheimer’s Disease Biomarkers in Hip Fracture Patients with Delirium - Karen Roksund Hov (Dementia and Geriatric Cognitive Disorders Extra, 2017)
Objectives: This study aimed to investigate the relationship between cerebrospinal fluid (CSF) S100B astrocyte-derived protein and delirium and to perform stratified analyses according to clinical and CSF markers of dementia. Methods: We performed a prospective cohort study in a university hospital setting. The participants were patients admitted for hip fracture (n = 98) or for elective surgery (n = 50). Delirium was assessed daily perioperatively in hip fracture patients using the Confusion Assessment Method. A consensus-based diagnosis of prefracture dementia was made using all available information. CSF was drawn at the onset of spinal anesthesia. S100B and phosphorylated tau (P-tau) concentrations were measured using electrochemiluminescence immunoassay and enzyme-linked immunosorbent assays, respectively. Results: In the hip fracture population (n = 98) there was no significant difference in CSF S100B concentrations between patients with ongoing preoperative (i.e., prevalent) delirium (n = 36, median [interquartile range] 1.11 μg/L [0.91–1.29]) and patients who never developed delirium (n = 46, 1.08 μg/L [0.92–1.28], p = 0.92). In patients without preoperative delirium, those who developed delirium postoperatively (i.e., incident delirium) (n = 16, 1.38 μg/L [1.08–1.62]) had higher concentrations of S100B than the 46 who never did (p = 0.013). This difference was confined to patients with pathological concentrations of P-tau (≥60 ng/L, n = 38). We also found that P-tau and S100B were correlated in CSF in the elective surgery patients. Conclusions: CSF S100B was elevated in patients with incident delirium who also had pathological levels of the Alzheimer disease biomarker P-tau, suggesting vulnerability caused by a preexisting process of astrocytic activation and tau pathology.